Acute Myocardial Infarction During Pregnancy and the Puerperium in the United States. Issue 3 (September 2019) - Smilowitz, N.R.; Gupta, N.; Guo, Y.; Zhong, J.; Weinberg, C.R.; Reynolds, H.R.; Bangalore, S.
Abstract : ( Mayo Clin Proc . 2018;93:1404–1414) Acute myocardial infarction (AMI) during pregnancy occurs infrequently yet accounts for 5% to 7% of maternal fatalities. In addition, there are significant risks to the developing fetus. The physiological changes in the cardiovascular system and the hypercoagulable state of pregnancy contribute to the increased risk of AMI during pregnancy. This study analyzed hospital admissions from a large national database to evaluate trends in the incidence, in-hospital management, and outcomes of AMI complicating pregnancy and the puerperium in the United States.